A two-dimensional titanium carbide@polyhedral transition metal sulfide composite material and its preparation method and application
Ti3C2 and NiS2 were combined by hydrothermal method to prepare NiS2@Ti3C2 composite material, which solved the problem of overlapping Ti3C2 electrode material and significantly improved its electrochemical performance and cycle stability.
Patent Information
- Application Number
- CN202310271504.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-20
AI Technical Summary
In the prior art, when Ti3C2 is used as a supercapacitor material, the overlapping problem is serious, which limits the electrochemical performance of high-density thin film electrodes.
The two-dimensional layered Ti3C2 was compounded with the transition metal sulfide NiS2 by hydrothermal method to prepare NiS2@Ti3C2 composite material, and Ti3C2 was used as a stable conductive substrate to recombine NiS2 polyhedral particles with high specific capacitance.
The specific capacitance, specific surface area, energy storage capacity, cycling performance and magnification characteristics of the composite material are improved, the electrochemical performance is significantly improved, and the cycling stability of the material is improved.
Smart Images

Figure CN116313568B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitor electrode materials and relates to a two-dimensional titanium carbide@polyhedron transition metal sulfide composite material and a preparation method and application thereof. Background Art
[0002] As a new type of energy storage device, supercapacitors have attracted widespread attention due to their outstanding advantages. Compared with traditional batteries, supercapacitors have many advantages such as short charging time, outstanding cycle stability, high safety, simple assembly, high power performance, and good reversibility, and have attracted widespread attention from scientific researchers. According to different energy storage mechanisms, supercapacitors can be divided into three categories: (1) Electric double layer capacitors (EDLCs), the typical electrode material is carbon material, such as activated carbon, carbon nanotubes, carbon nanofibers, porous carbon, etc., which are low in cost and good in stability. However, due to the limited contact area between carbon materials and electrolytes, the improvement of their energy storage performance is limited; (2) Faradaic pseudocapacitors or pseudocapacitors (PCs), the typical electrode materials are metal oxides and conductive polymers; (3) Hybrid supercapacitors (HCs), whose energy storage principle is based on the combination of the first two, and the two electrodes use different electrode materials. Among them, the positive electrode generally uses metal oxides or conductive polymers, and the negative electrode is mostly carbon-based materials.
[0003] The emerging two-dimensional titanium carbide (Ti3C2) in recent years is a graphene-like sheet material. Ultra-thin two-dimensional nanosheets have super catalytic, photovoltaic and electrochemical properties due to their unique morphology, small particle size, large surface-to-volume ratio and atomic-level sheet thickness. They have been widely used in functional ceramics, photocatalysis, lithium-ion batteries, solar cells, biosensors, etc. Ti3C2 is considered to be a very promising supercapacitor electrode material due to its special two-dimensional layered structure, large specific surface area, excellent conductivity, excellent electrochemical energy storage performance and excellent mechanical properties. Ti3C2 has excellent capacity retention, but its theoretical specific capacity is relatively low, and the problem of overlapping two-dimensional titanium carbide seriously limits the electrochemical performance of high-density thin film electrodes.
[0004] At the same time, transition metal sulfides have attracted attention in a wide range of applications such as supercapacitors, photoelectron catalysis, batteries, and sensors. It is particularly noteworthy that NiS2, as a common transition metal sulfide material, has low electronegativity and high electrochemical activity, so it can be used as a pseudocapacitor with excellent performance. However, NiS2 eventually suffers from large energy decay due to the expansion and contraction of its structure during the charge / discharge cycle. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material and its preparation method and application, so as to improve the problem of serious overlap of Ti3C2 as a capacitor material in the prior art, which limits the electrochemical performance of high-density thin film electrodes.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material comprises the following steps:
[0008] Step 1, after LiF is uniformly dispersed in HCl solution, Ti3AlC2 is added, and after heating and magnetic stirring for reaction, the reaction system is centrifuged to obtain a centrifugal product, the centrifugal product is placed in water, and stirred until the centrifugal product is dissolved to obtain solution A; solution A is subjected to ultrasonic treatment after oxygen removal under vacuum environment to obtain solution B, solution B is centrifuged to obtain a supernatant, and the supernatant is freeze-dried to obtain a monolayer Ti3C2 powder;
[0009] Step 2, adding nickel chloride hexahydrate and sodium thiosulfate to water, adding a monolayer of Ti3C2 powder after magnetic stirring, heating with magnetic stirring for hydrothermal reaction, obtaining a reaction precipitate, washing the reaction precipitate, dissolving the washed reaction precipitate in water to form a solution C, and vacuum freeze-drying the solution C to obtain NiS2@Ti3C2.
[0010] A further improvement of the present invention is:
[0011] Preferably, in step 1, the mixing mass ratio of LiF and Ti3AlC2 is 1:1.
[0012] Preferably, in step 1, the heating magnetic stirring reaction temperature is 35° C., and the magnetic stirring speed is 300 rpm / min.
[0013] Preferably, in step 1, the rotation speed of the two centrifugations is 3500 rpm / min.
[0014] Preferably, in step 2, the molar ratio of nickel chloride to thiosulfate is 1:1.
[0015] Preferably, in step 2, the mixing molar ratio of nickel chloride hexahydrate and monolithic titanium carbide powder is 0.9:(0.5-1).
[0016] Preferably, in step 2, the reaction temperature is 160° C. and the reaction time is 8 h.
[0017] Preferably, in step 2, the freeze-drying temperature is -45°C and the freeze-drying pressure is 1Pa.
[0018] A two-dimensional titanium carbide@polyhedral transition metal sulfide composite material prepared by any one of the above preparation methods, wherein the two-dimensional titanium carbide@polyhedral transition metal sulfide is NiS2@Ti3C2, and NiS2 is composited on lamellar Ti3C2 in the form of nano-polyhedrons.
[0019] An application of the above-mentioned two-dimensional titanium carbide@polyhedral transition metal sulfide composite material is used to prepare supercapacitors.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention discloses a method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material, wherein the method uses a freeze-drying method to peel off a two-dimensional layered Ti3C2, and uses a hydrothermal method to compound the two-dimensional layered Ti3C2 and transition metal sulfide NiS2 to prepare a NiS2@Ti3C2 composite material, wherein Ti3C2 is used as a stable conductive substrate and is compounded with high specific capacitance NiS2 polyhedral particles, and the composite material has a higher specific capacitance and specific surface area by utilizing the synergistic effect of Ti3C2 and NiS2, and improves the electrochemical properties of the composite electrode material such as energy storage capacity, cycle performance and rate characteristics. The morphology and structure of the material are characterized by using a field emission scanning electron microscope (SEM), a transmission electron microscope (TEM), an X-ray diffraction (XRD), and a Raman spectrometer, and a series of electrochemical performance tests are performed on the prepared NiS2@Ti3C2 composite electrode material in a 3.0M (changed to 3M) NaOH electrolyte. The results show that at a scan rate of 2mV / s, the maximum capacitance of the NiS2@Ti3C2 composite material reaches 1489.28F / g, and it exhibits excellent cycle stability. Under the condition of a current density of 2A / g, after 1000 cycles of constant current charge and discharge, the capacity still has 87.85% of the original capacity. This shows that the NiS2@Ti3C2 composite material has excellent cycle stability. In addition, the composite material has a low internal resistance, and its good electrochemical properties make the two-dimensional titanium carbide@polyhedral transition metal sulfide composite material an ideal supercapacitor electrode material.
[0022] Furthermore, through the analysis of electrochemical performance tests, it was shown that the 1:0.8 NiS2@Ti3C2 composite material has the best electrochemical performance, and 1:0.8 is the optimal ratio for synthesizing composite materials; NiS2@Ti3C2 composite material, using the synergistic effect of Ti3C2 and NiS2, significantly increases the stability of the composite material, reduces the expansion and collapse of the material, and achieves a significant improvement in its electrochemical properties such as specific capacitance, conductivity, rate characteristics and cycle stability.
[0023] Furthermore, the present invention successfully peels off the multilayer Ti3C2 material into a few-layer material through freeze-drying, making it a truly layered two-dimensional material, obtaining a larger specific surface area and exerting excellent conductivity.
[0024] The present invention also discloses a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material, which is composited on lamellar Ti3C2 in the form of nano-polyhedrons. In the process of repeated stacking of lamellar Ti3C2 organized by granular NiS2, the lamellar Ti3C2 prevents the expansion and contraction of the structure of NiS2 during the charge / discharge cycle, thereby reducing its cycle stability and improving the problem of low specific capacitance of Ti3C2-based composite electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of NiS2 and NiS2@Ti3C2 samples;
[0026] Figure 2 SEM image of NiS2@Ti3C2 sample;
[0027] Figure 3 TEM image of NiS2@Ti3C2 sample;
[0028] Figure 4 CV curves of NiS2@Ti3C2 at different scan rates with a ratio of 1:0.5 and 1:0.8 respectively;
[0029] Figure 5 CV curves of NiS2 at different scan rates, CV curves of NiS2@Ti3C2, NiS2, and Ti3C2 at a scan rate of 2 mV / s at 1:0.8;
[0030] Figure 6 GCD curves of NiS2 at different current densities, GCD curves of NiS2@Ti3C2, NiS2, and Ti3C2 at a current density of 0.5A / g at a ratio of 1:0.8;
[0031] Figure 7 EIS graphs of NiS2@Ti3C2 with different proportions. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0033] In the description of the present invention, it should be noted that the orientations or positional relationships indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection or a detachable connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0034] The invention discloses a method for preparing a NiS2@Ti3C2 composite material by a hydrothermal method, comprising the following steps:
[0035] Step 1, preparation of two-dimensional Ti3C2 powder
[0036] Add 2g of LiF to 20mL of 9M HCl and stir for 10min. The container used is a polytetrafluoroethylene beaker. After LiF is evenly dispersed in the HCl solution, add 2g of Ti3AlC2, use a heated magnetic stirrer, set the temperature to 35℃, the speed to 300rpm / min, and stir continuously for 24h. After the reaction is completed, use a high-speed centrifuge, set the speed to 3500rpm / min, centrifuge for 2min, and centrifuge and wash with deionized water several times until the pH value of the sample washing solution is greater than 6. Add the precipitate after centrifugation to 300mL of ultrapure water and stir until the precipitate is completely dissolved to obtain solution A. Then, deoxygenate solution A for 2h and ultrasonicate for 1h in a vacuum environment. Deoxygenate before ultrasonic treatment to prevent product oxidation. After completion, use a high-speed centrifuge to centrifuge for 1h, set the speed to 3500rpm / min. After centrifugation, take the supernatant and freeze-dry for 24h to obtain a monolayer Ti3C2 powder.
[0037] Step 2, Synthesis of NiS2@Ti3C2 Composites
[0038] 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate were slowly added to a beaker containing 30mL of deionized water, and magnetically stirred at 500rpm / min for 20min, and then (0.5-1)mmol of monolayer titanium carbide powder was slowly added, and magnetically stirred at 500rpm / min for 20min to mix evenly. The mixed solution was transferred to a 100mL hydrothermal kettle and reacted at 160℃ for 8h. During this process, nickel chloride hexahydrate and sodium thiosulfate gradually reacted to form polyhedral NiS2 particles, which were then compounded in the monolayer titanium carbide powder. Then the lower precipitate was taken out, the black precipitate was washed with acetone, anhydrous ethanol and deionized water, and the precipitate was dissolved in deionized water to form solution C, and solution C was transferred to a vacuum freeze dryer and freeze-dried at 1Pa atmospheric pressure and -45℃ for 48h to obtain NiS2@Ti3C2.
[0039] The final NiS2@Ti3C2 composite material is a nano-polyhedral NiS2 composited on lamellar Ti3C2.
[0040] Step 3: Performance testing and comparison
[0041] The monolithic Ti3C2 powder, nano-NiS2 material and NiS2@Ti3C2 samples obtained in steps one, two and three were subjected to electrochemical performance tests such as CV, GCD, ETS, and their morphological structures were characterized by SEM, TEM, etc. The comparison shows that the performance of NiS2@Ti3C2 is significantly better than that of monolithic Ti3C2 powder and pure phase nano-NiS2.
[0042] The present invention uses nickel chloride hexahydrate and sodium thiosulfate as raw materials and successfully synthesizes a NiS2@Ti3C2 composite material on the surface of Ti3C2 by a hydrothermal method. Electrochemical tests show that the electrochemical performance of the composite NiS2@Ti3C2 material has been significantly improved. When the scanning rate is 2mV / s, the capacity of NiS2@Ti3C2 reaches 1489.28F / g, and it shows significant chemical stability. When the current density is 2A / g, the capacity still has 87.85% of the original capacity after constant current charge and discharge for 1000 times.
[0043] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0044] Comparative Example: Preparation of Nano NiS2 Materials
[0045] Slowly add 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate to a beaker containing 30mL of deionized water, and stir magnetically at 500rpm / min for 20min to mix them evenly. Transfer the evenly mixed solution into a 100mL hydrothermal kettle and react at 160℃ for 8h. Then take out the lower precipitate, use a high-speed centrifuge, and centrifuge and wash the black precipitate twice with anhydrous ethanol and deionized water, respectively, at a speed of 4500rpm / min, each time for 5min. After centrifugation, transfer the black precipitate to a vacuum drying oven and dry it at 1Pa atmospheric pressure and 60℃ for 24h to obtain a nano-polyhedral NiS2 material.
[0046] Example 1
[0047] Step 1, preparation of two-dimensional Ti3C2 powder
[0048] Add 2g of LiF to 20mL of 9M HCl and stir for 10min. The container used is a polytetrafluoroethylene beaker. After LiF is evenly dispersed in the HCL solution, add 2g of Ti3AlC2, use a heated magnetic stirrer, set the temperature to 35℃, the speed to 300rpm / min, and stir continuously for 24h. After the reaction is completed, use a high-speed centrifuge, set the speed to 3500rpm / min, centrifuge for 2min, centrifuge and wash with deionized water several times until the sample pH is greater than 6, add the centrifuged precipitate to 300mL of ultrapure water, and stir until the precipitate is completely dissolved. Then deoxygenate the solution for 2h and ultrasonicate for 1h in a vacuum environment. After completion, use a high-speed centrifuge to centrifuge for 1h, set the speed to 3500rpm / min. After centrifugation, take the supernatant and freeze-dry for 24h to obtain a monolayer Ti3C2 powder.
[0049] Step 2, Synthesis of NiS2@Ti3C2 Composites
[0050] Slowly add 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate to a beaker containing 30mL of deionized water, stir magnetically at 500rpm / min for 20min, then slowly add 0.5mmol of monolayer titanium carbide, stir magnetically at 500rpm / min for 20min to mix evenly. Transfer the evenly mixed solution to a 100mL hydrothermal kettle and react at 160℃ for 8h. Then take out the lower precipitate, wash the black precipitate with acetone, anhydrous ethanol and deionized water, dissolve the precipitate in deionized water, transfer to a vacuum freeze dryer, freeze-dry at 1Pa atmospheric pressure and -45℃ for 48h to obtain NiS2@Ti3C2.
[0051] Step 3: Performance testing and comparison
[0052] The monolithic Ti3C2 powder, nano-NiS2 material and NiS2@Ti3C2 sample obtained in step 1, comparative example and step 2 were subjected to electrochemical performance tests such as CV, GCD and ETS, and their morphological structures were characterized by SEM and TEM.
[0053] Example 2
[0054] Step 1, preparation of two-dimensional Ti3C2 powder
[0055] Add 2g of LiF to 20mL of 9M HCl and stir for 10min. The container used is a polytetrafluoroethylene beaker. After LiF is evenly dispersed in the HCL solution, add 2g of Ti3AlC2, use a heated magnetic stirrer, set the temperature to 35℃, the speed to 300rpm / min, and stir continuously for 24h. After the reaction is completed, use a high-speed centrifuge, set the speed to 3500rpm / min, centrifuge for 2min, centrifuge and wash with deionized water several times until the sample pH is greater than 6, add the centrifuged precipitate to 300mL of ultrapure water, and stir until the precipitate is completely dissolved. Then deoxygenate the solution for 2h and ultrasonicate for 1h in a vacuum environment. After completion, use a high-speed centrifuge to centrifuge for 1h, set the speed to 3500rpm / min. After centrifugation, take the supernatant and freeze-dry for 24h to obtain a monolayer Ti3C2 powder.
[0056] Step 2, Synthesis of NiS2@Ti3C2 Composites
[0057] Slowly add 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate to a beaker containing 30mL of deionized water, stir magnetically at 500rpm / min for 20min, then slowly add 0.7mmol of monolayer titanium carbide, stir magnetically at 500rpm / min for 20min to mix evenly. Transfer the mixed solution to a 100mL hydrothermal kettle and react at 160℃ for 8h. Then take out the lower precipitate, wash the black precipitate with acetone, anhydrous ethanol and deionized water, dissolve the precipitate in deionized water, transfer to a vacuum freeze dryer, freeze-dry at 1Pa atmospheric pressure and -45℃ for 48h to obtain NiS2@Ti3C2.
[0058] Step 3: Performance testing and comparison
[0059] The monolithic Ti3C2 powder, nano-NiS2 material and NiS2@Ti3C2 sample obtained in step 1, comparative example and step 2 were subjected to electrochemical performance tests such as CV, GCD and ETS, and their morphological structures were characterized by SEM and TEM.
[0060] See also Figure 1 for Figure 1XRD spectra and local magnified spectra of NiS2 and NiS2@Ti3C2; observing the XRD spectrum of NiS2@Ti3C2 (left figure), the diffraction peaks of Ti3C2 can be observed at 2θ=7.3° and 60.6°, corresponding to its (002) and (110) crystal planes; from its local magnified figure (right figure), it can be clearly observed that the diffraction peaks observed at 2θ=31.6° and 55.3° correspond to the (311) and (440) crystal planes of NiS2, respectively, which indicates the successful synthesis of the NiS2@Ti3C2 composite.
[0061] Figure 2 This is the SEM picture of NiS2@Ti3C2. Figure 2 a It can be observed that a large amount of NiS2 is loaded on the surface of the monolithic Ti3C2. The results show that the growth of NiS2 on two-dimensional Ti3C2 is achieved through this experimental research, and the NiS2@Ti3C2 nanocomposite material is successfully prepared. Figure 2 It can be more clearly observed in b that the small polyhedral particles of NiS2 are uniformly loaded on the lamellar Ti3C2, and NiS2 presents a uniform, monodispersed polyhedral particle morphology with a relatively smooth surface. The composite of the two materials can effectively inhibit the self-assembly and stacking of Ti3C2, and the addition of NiS2 can increase the specific surface area of the matrix material Ti3C2, giving it additional active sites, thereby improving the electrochemical performance of the material.
[0062] Figure 3 This is the transmission spectrum of NiS2@Ti3C2. Figure 3 As can be seen in Figure (a), the two-dimensional lamellar is the Ti3C2 matrix, and the small black particles are NiS2. It can be seen more clearly in (3b) at high magnification that the NiS2 particles are cubic and the NiS2 particle size is about 20nm. The successful loading of polyhedral small particles NiS2 on the surface of the monolithic Ti3C2 was further proved by SEM and TEM tests.
[0063] Figure 4 is the cyclic voltammetry (CV) graph of the NiS2@Ti3C2 electrode with a ratio of 1:0.5 at scan rates of 10, 20, and 50 mV / s; Figure 4 (b) is the cyclic voltammetry (CV) curve of the NiS2@Ti3C2 electrode with a ratio of 1:0.8 at scan rates of 2, 5, and 10 mV / s; by comparison, it can be clearly seen that the NiS2@Ti3C2 electrode material with a ratio of 1:0.8 has a more obvious redox peak and a larger CV enclosed area, thus proving that the NiS2@Ti3C2 electrode material with a ratio of 1:0.8 has better electrochemical performance.
[0064] Figure 5 (a) Cyclic voltammetry (CV) curves of NiS2 at 10, 20, and 40 mV / s; Figure 5 (b) is the cyclic voltammetry (CV) curve of NiS2@Ti3C2, NiS2 and Ti3C2 electrodes with a ratio of 1:0.8 at a scan rate of 20 mV / s. Figure 5 (b) It can be seen that NiS2@Ti3C2 has the most obvious redox peak, which proves the pseudocapacitive behavior of its material and is also the reason why the composite material has a good specific capacity. Compared with Ti3C2 and NiS2, the NiS2@Ti3C2 electrode has a larger CV enclosed area, indicating that the NiS2@Ti3C2 composite electrode has a larger specific capacity. The formula calculated that at a scan rate of 2mV / s, the specific capacity of NiS2@Ti3C2 is as high as 1489.28F / g.
[0065] Figure 6 (a) is the GCD curve of NiS2 electrode at current density of 0.5, 1, and 2 A / g. Figure 6 (b) shows the GCD curves of NiS2@Ti3C2, NiS2 and Ti3C2 at a current density of 0.5A / g. It can be seen that the NiS2@Ti3C2 electrode material has the longest discharge time at the same current density, proving its excellent capacitive performance. As the current density continues to increase, the discharge time of the electrode material gradually becomes shorter, which is usually attributed to the fact that the electrolyte ions on the electrode surface are not fully diffused at high current densities. Calculated by the formula, at current densities of 1, 2 and 5A / g, the mass specific capacity of NiS2@Ti3C2 is 1382.28, 1240.96, and 1042.44F / g, respectively.
[0066] Figure 7 The graph shows the variation of specific capacity with the number of cycles after 1000 cycles of Ti3C2, NiS2@Ti3C2 and Ti3C2 electrodes at a current density of 2A / g. As can be seen from the figure, after 1000 cycles, the capacity retention rates of Ti3C2, NiS2@Ti3C2 and NiS2 are 100%, 87.85% and 78.37%, respectively. This result shows that compared with NiS2, NiS2@Ti3C2 electrode material has better cycle stability. This may be because, using Ti3C2 as a conductive matrix, the volume expansion and contraction of NiS2 monomers during multiple cycle tests can be improved, the destruction and collapse of the transition metal sulfide structure can be reduced, and NiS2 is attached to the surface of Ti3C2, which improves the conductivity of the composite material, thereby improving the cycle stability of the composite material.
[0067] Example 3
[0068] Step 1: Preparation of two-dimensional Ti3C2 powder
[0069] Add 2g of LiF to 20mL of 9M HCl and stir for 10min. The container used is a polytetrafluoroethylene beaker. After LiF is evenly dispersed in the HCL solution, add 2g of Ti3AlC2, use a heated magnetic stirrer, set the temperature to 35℃, the speed to 300rpm / min, and stir continuously for 24h. After the reaction is completed, use a high-speed centrifuge, set the speed to 3500rpm / min, centrifuge for 2min, centrifuge and wash with deionized water several times until the sample pH is greater than 6, add the centrifuged precipitate to 300mL of ultrapure water, and stir until the precipitate is completely dissolved. Then deoxygenate the solution for 2h and ultrasonicate for 1h in a vacuum environment. After completion, use a high-speed centrifuge to centrifuge for 1h, set the speed to 3500rpm / min. After centrifugation, take the supernatant and freeze-dry for 24h to obtain a monolayer Ti3C2 powder.
[0070] Step 2, Synthesis of NiS2@Ti3C2 Composites
[0071] Slowly add 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate to a beaker containing 30mL of deionized water, stir magnetically at 500rpm / min for 20min, then slowly add 0.9mmol of monolayer titanium carbide, stir magnetically at 500rpm / min for 20min to mix evenly. Transfer the mixed solution to a 100mL hydrothermal kettle and react at 160℃ for 8h. Then take out the lower precipitate, wash the black precipitate with acetone, anhydrous ethanol and deionized water, dissolve the precipitate in deionized water, transfer to a vacuum freeze dryer, freeze-dry at 1Pa atmospheric pressure and -45℃ for 48h to obtain NiS2@Ti3C2.
[0072] Step 3: Performance testing and comparison
[0073] The monolithic Ti3C2 powder, nano-NiS2 material and NiS2@Ti3C2 sample obtained in step 1, comparative example and step 3 were subjected to electrochemical performance tests such as CV, GCD and ETS, and their morphological structures were characterized by SEM and TEM.
[0074] Example 4
[0075] Step 1, preparation of two-dimensional Ti3C2 powder
[0076] Add 2g of LiF to 20mL of 9M HCl and stir for 10min. The container used is a polytetrafluoroethylene beaker. After LiF is evenly dispersed in the HCL solution, add 2g of Ti3AlC2, use a heated magnetic stirrer, set the temperature to 35℃, the speed to 300rpm / min, and stir continuously for 24h. After the reaction is completed, use a high-speed centrifuge, set the speed to 3500rpm / min, centrifuge for 2min, centrifuge and wash with deionized water several times until the sample pH is greater than 6, add the centrifuged precipitate to 300mL of ultrapure water, and stir until the precipitate is completely dissolved. Then deoxygenate the solution for 2h and ultrasonicate for 1h in a vacuum environment. After completion, use a high-speed centrifuge to centrifuge for 1h, set the speed to 3500rpm / min. After centrifugation, take the supernatant and freeze-dry for 24h to obtain a monolayer Ti3C2 powder.
[0077] Step 2, Synthesis of NiS2@Ti3C2 Composites
[0078] Slowly add 0.9mmol of nickel chloride hexahydrate and 0.9mmol of sodium thiosulfate to a beaker containing 30mL of deionized water, stir magnetically at 500rpm / min for 20min, then slowly add 0.5mmol of monolayer titanium carbide, stir magnetically at 500rpm / min for 20min to mix evenly. Transfer the evenly mixed solution to a 100mL hydrothermal kettle and react at 160℃ for 8h. Then take out the lower precipitate, wash the black precipitate with acetone, anhydrous ethanol and deionized water, dissolve the precipitate in deionized water, transfer to a vacuum freeze dryer, freeze-dry at 1Pa atmospheric pressure and -45℃ for 48h to obtain NiS2@Ti3C2.
[0079] Step 4: Performance testing and comparison
[0080] The monolithic Ti3C2 powder, nano-NiS2 material and NiS2@Ti3C2 sample obtained in step 1, comparative example and step 3 were subjected to electrochemical performance tests such as CV, GCD and ETS, and their morphological structures were characterized by SEM and TEM.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material, characterized in that: The following steps are involved: Step 1, after LiF is uniformly dispersed in HCl solution, Ti3AlC2 is added, heating and magnetic stirring are performed for reaction, the reaction system is centrifuged to obtain a centrifugal product, the centrifugal product is placed in water, and stirred until the centrifugal product is dissolved to obtain solution A; Solution A was deoxygenated under vacuum and then ultrasonically treated to obtain solution B, solution B was centrifuged to obtain a supernatant, and the supernatant was freeze-dried to obtain a monolayer Ti3C2 powder; Step 2, adding nickel chloride hexahydrate and sodium thiosulfate to water, adding a monolayer of Ti3C2 powder after magnetic stirring, heating with magnetic stirring for hydrothermal reaction, obtaining a reaction precipitate, washing the reaction precipitate, dissolving the washed reaction precipitate in water to form a solution C, and vacuum freeze-drying the solution C to obtain NiS2@Ti3C2.
2. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 1, the mixing mass ratio of LiF and Ti3AlC2 is 1:
1.
3. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 1, the heating magnetic stirring reaction temperature is 35° C., and the magnetic stirring speed is 300 rpm / min.
4. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 1, the rotation speed of the two centrifugations was 3500 rpm / min.
5. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 2, the molar ratio of nickel chloride to thiosulfate is 1:
1.
6. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 2, the mixing molar ratio of nickel chloride hexahydrate and monolithic titanium carbide powder is 0.9:(0.5-1).
7. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 2, the reaction temperature is 160° C. and the reaction time is 8 h.
8. The method for preparing a two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 1, characterized in that: In step 2, the freeze-drying temperature is -45°C and the freeze-drying pressure is 1Pa.
9. A two-dimensional titanium carbide@polyhedral transition metal sulfide composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The two-dimensional titanium carbide@polyhedral transition metal sulfide is NiS2@Ti3C2, and NiS2 is composited on lamellar Ti3C2 in the form of nano-polyhedrons.
10. An application of the two-dimensional titanium carbide@polyhedral transition metal sulfide composite material according to claim 9, characterized in that: Used to prepare supercapacitors.
Citation Information
Patent Citations
Preparation method of transition metal sulfide / graphene composite material
CN110047660A
Nanotube NiCo2S4@titanium carbide composite material and preparation method and application thereof
CN111916288A